An Investigation of Waiting Times of Patients Admitted to the General Surgery Clinic from an Emergency Department - Suna Eraybar Atmaca; Halil Kaya; Melih Yüksel; Faruk Çavdar; Yeşim İşler (Journal of Contemporary Medicine, 2019)
AbstractBackground/Aims:The study aimed to determine the waiting times of the patients admitted to the general surgery clinic from an emergency department and to investigate the effectiveness of services.Methods:1564 patients over the age of 18 admitted to the General Surgery Clinic from the emergency department of Health University BursaTraining and Research Hospital between 01.01.2018 and 31.12.2018 were included. Age, gender, admission and waiting times, the diagnoses, and surgical history or hospitalization were retrospectively analyzed. The difference between the admission time to the emergency department and the admission time to the general surgery clinic was accepted as waiting time.Results:56% of the patients (n: 876) were male and the mean age was 49.9. The mean waiting time in the emergency department was 440.85 minutes and the mean hospital stay was 4.67 days. The minimum waiting time was in abdominal trauma (249.49 min) whereas the longest waiting time was in mesenteric ischemia (732.27 min) in the emergency department.Conclusions: We believe that having a separate and senior team in emergency services of work-intensive departments such as general surgery will contribute to shortening waiting times and providing faster and more effective health care.